Oil-containing antirust coating and preparation method thereof

By using the reaction of aromatic sulfonyl chloride and zinc powder to generate aromatic sulfinic acid in anti-rust coatings, the problem of unsatisfactory corrosion protection effect of existing anti-corrosion coatings on metal substrates is solved, and high adhesion and long life are achieved. Anti-corrosion effect, while effectively decomposing oil stains and forming a stable passivation layer.

CN119331515APending Publication Date: 2025-01-21SICHUAN JIANGYUAN HONGSHENG TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310884303.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The corrosion protection effect of existing anticorrosion coatings on metal substrates is not ideal, and they are costly, contain heavy metals or toxic substances, pose a risk of environmental pollution, and it is difficult to effectively remove oil stains, resulting in reduced adhesion of coatings, prone to cracking and falling off, and shorten service life. .

Method used

A kind of oil -proof coating with oil, its main agent includes hydroxye ethyl cellulose, a silicane coupling agent, emulsifier, dispersant, and ultra -fine composite titanium pink with epoxy epoxy group. The mixture of zinc powder generates sulfonal sulfonic acid through the reaction of sulfonal chloride and zinc powder, forming a stable sulfurized compound to improve the adhesion and corrosion effect of the coating.

Benefits of technology

It effectively improves the adhesion and anti-corrosion effect of the coating, extends the service life of the coating, and decomposes oil stains on the surface of the steel substrate through emulsifiers and aromatic sulfinic acid to form an effective passivation layer, avoiding coating shedding and corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The invention discloses an oil-containing antirust coating, and belongs to the technical field of coatings, the oil-containing antirust coating comprises a main agent and an auxiliary agent, the main agent comprises hydroxyethyl cellulose, a silane coupling agent with an epoxy functional group, an emulsifier, a dispersant, superfine composite titanium dioxide, superfine ferrophosphorus powder, superfine barium sulfate, superfine zeolite powder, talcum powder, a nano pigment and a film forming substance; the auxiliary agent is aryl sulfonyl chloride, zinc powder is added into the aryl sulfonyl chloride, the mixture is uniformly stirred and then added into the main agent, and the aryl sulfonyl chloride in the auxiliary agent is partially converted into aryl sulfinic acid. Aryl sulfonyl chloride can be reduced into arylsulfinic acid under the action of zinc, so that the passivated steel surface is anticorrosive, the adhesive force of a coating is improved, and the service life of the coating is prolonged. Oil stains on the surface of a steel base material are decomposed through the emulsifier and the arylsulfinic acid, and the coating permeates into the surface of the base material to form an effective passivation layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to an oil-containing anti-rust coating and a preparation method thereof. Background Art

[0002] At present, there are high anti-corrosion requirements in ship anti-corrosion, oil storage tanks, oil platforms, container anti-corrosion, railways, highway bridges, steel structures, etc. Generally, for anti-corrosion coatings, traditional protective coatings are limited by their own material properties and processes, and the corrosion protection effect on metal substrates is often not ideal. The cost of individual outstanding performance is very high, which reduces the cost performance of the coating. In addition, a considerable part of the coating contains heavy metals or toxic substances such as lead, zinc or chromate, which poses a certain risk of environmental pollution and consumes a large amount of non-renewable resources, which is not conducive to the sustainable development of social economy. Therefore, the development of various new types of long-term and environmentally friendly anti-corrosion coatings has become a new hot spot. The oil stains on the metal surfaces of machinery, parts, etc. are mostly anti-rust oils, anti-rust greases, vapor phase rust inhibitors and water-soluble corrosion inhibitors. Because the components of this type of oil stains are relatively complex, they adhere closely to the metal, and over a long period of time, the components evaporate, self-polymerize, and even undergo physical and chemical changes, making them difficult to clean.

[0003] The steel processing process cannot completely avoid the generation of oil pollution. There is a large amount of oil pollution on drilling and processing equipment during the maintenance process. The oil pollution cannot be completely removed during the application of anti-rust paint, resulting in reduced adhesion of the coating. Under the action of external force or changes in ambient temperature, the coating is prone to cracking and falling off, shortening the service life of the coating. Existing anti-corrosion coatings generally use the method of adding zinc powder for electrochemical corrosion protection. However, zinc will produce zinc oxide ions during the reaction. The ions are weakly alkaline and can easily cause the water-based coating to fall off, reducing the anti-corrosion effect. Summary of the invention

[0004] In view of the above problems, the present invention aims to solve the above problems. One object of the present invention is to provide an oil-based anti-rust paint that solves the above problems.

[0005] The solution adopted in this embodiment is: an oil-containing anti-rust paint, including a main agent and an auxiliary agent, wherein the main agent formula is: hydroxyethyl cellulose, a silane coupling agent with epoxy functional groups, an emulsifier, a dispersant, and ultrafine composite titanium dioxide, ultrafine ferrophosphorus powder, ultrafine barium sulfate, ultrafine zeolite powder, talcum powder, nano pigments, and film-forming substances; The chemical formula of the additive is The aromatic sulfonyl chloride is added with zinc powder, stirred evenly and then added to the main agent, so that the aromatic sulfonyl chloride in the auxiliary agent is partially converted into aromatic sulfinic acid.

[0006] The preferred technical solution is that when the aromatic sulfonyl chloride and the zinc powder are stirred, the temperature is controlled between 130°C and 140°C, and the stirring time is 8-10 minutes.

[0007] The preferred technical solution is that graphene is added to the auxiliary agent, and graphene and zinc powder are added to aromatic sulfonyl chloride at the same time and stirred evenly. During stirring, the stirring kettle is connected to a positive power supply, the stirring rod is connected to a negative power supply, and the stirring kettle and the stirring rod are insulated, and the input voltage is controlled at 60V.

[0008] The preferred technical solution is that, according to the mass percentage, the content of the main agent is 93%-95%, the content of the auxiliary agent is 5%-7%, the content of zinc powder in the auxiliary agent is 4%-5%, and the ratio of aromatic sulfonyl chloride to aromatic sulfinic acid is 0.5-0.8:1.

[0009] The preferred technical solution is that the mass percentages of the components in the main agent are: 0.3%-0.7% hydroxyethyl cellulose, 1.2%-6.2% silane coupling agent with epoxy functional group, 0.5%-1% emulsifier, 0.8%-1.5% dispersant, 1%-2% ultrafine composite titanium dioxide, 0.6%-1% ultrafine ferrophosphorus powder, 2%-4% ultrafine barium sulfate, 3%-5% ultrafine zeolite powder, 4%-6% talc, 0.5%-2% nano pigment, and 30%-50% film-forming substance.

[0010] A method for preparing an oil-containing anti-rust coating, step S00: putting a dispersant, ultrafine composite titanium dioxide, ultrafine ferrophosphorus powder, ultrafine barium sulfate, ultrafine zeolite powder, and talcum powder into a device according to mass fractions and mixing them evenly; Step S10: adding hydroxyethyl cellulose, a silane coupling agent having an epoxy functional group, a film-forming substance, an emulsifier, and deionized water to the above mixture, mixing and stirring the mixture evenly, and ultrasonically treating the mixture; Step S20: adding zinc powder to arylsulfonyl chloride and stirring evenly, controlling the temperature between 130°C and 140°C, and stirring for 8-10 minutes; Step S30: mixing the uniformly mixed auxiliary agent and the main agent together, stirring at high speed to uniformly obtain the coating after filtering; Step S40: adding nano pigments of different colors into the above coating to obtain coatings of different colors.

[0011] Further, in step S20, graphene is added, and graphene and zinc powder are added to aromatic sulfonyl chloride at the same time and stirred evenly. During stirring, the stirring kettle is connected to a positive power supply, the stirring rod is connected to a negative power supply, and the stirring kettle and the stirring rod are insulated, and the input voltage is controlled at 60V.

[0012] The oil-based anti-rust paint of the present invention has the following technical effects: The oil-containing anti-rust paint of the present application includes a main agent and an auxiliary agent, wherein the main agent formula is: hydroxyethyl cellulose, a silane coupling agent with epoxy functional groups, an emulsifier, a dispersant, and ultrafine composite titanium dioxide, ultrafine ferrophosphorus powder, ultrafine barium sulfate, ultrafine zeolite powder, talcum powder, nano pigments, and film-forming substances; the auxiliary agent is arylsulfonyl chloride, and the arylsulfonyl chloride is added to the main agent after adding zinc powder and stirring evenly, so that the arylsulfonyl chloride in the auxiliary agent is partially converted into arylsulfinic acid. Aromatic sulfonyl chloride will be reduced to arylsulfinic acid under the action of zinc, which will passivate the steel surface to achieve corrosion protection, improve the adhesion of the coating, and extend the service life of the coating. The oil stains on the surface of the steel substrate are decomposed by the emulsifier and arylsulfinic acid, and the coating penetrates into the surface of the substrate to form an effective passivation layer. Implementation

[0013] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention is clearly and completely described. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments in this application and the features in the embodiments can be combined with each other arbitrarily without conflict.

[0014] The oil-based anti-rust paint is described in detail below in conjunction with the embodiments. Example

[0015] The oil-containing anti-rust coating provided in this embodiment has a total mass of 300g, and each component is mixed according to the total mass fraction. 1.1% of dispersant, 1.4% of ultrafine composite titanium dioxide, 0.8% of ultrafine ferrophosphorus powder, 3% of ultrafine barium sulfate, 3% of ultrafine zeolite powder, and 5% of talcum powder are put into the device and mixed evenly.

[0016] The above mixture is added with 0.4% hydroxyethyl cellulose, 3.4% silane coupling agent with epoxy functional group, 45% film-forming substance, 0.6% emulsifier and deionized water, mixed and stirred evenly and ultrasonically treated to obtain mixture A. The film-forming substance includes 29% water-based phenolic epoxy resin and 16% water-based polyurethane. The stirring speed of the stirrer is between 800-1200r / min. The ultrasonic treatment temperature is 0-35℃ and the ultrasonic treatment time is 8-14h.

[0017] Add 1.5% of arylsulfonyl chloride to 5.2% of zinc powder and stir evenly, control the temperature at 140°C, and stir for 10 minutes to obtain substance B. The chemical formula of the reaction between arylsulfonyl chloride and zinc is: . Aromatic sulfinic acid has a stronger sulfonation ability than aromatic sulfonyl chloride because it can form more stable sulfonated compounds in water. Aromatic sulfinic acid has a higher degree of sulfonation and can form more sulfonated compounds, thereby increasing its sulfonation ability. Aromatic sulfinic acid is more stable than aromatic sulfonyl chloride and is not easy to decompose or lose its sulfonation ability. The sulfonated compounds formed by aromatic sulfinic acid in water can remain stable in a humid environment, while aromatic sulfonyl chloride needs to be in a dry environment to remain stable.

[0018] Mix substance A and substance B together, stir at high speed and filter to obtain the coating. The stirring speed of the mixer is between 3000-4000r / min. The filter aperture is 130 mesh.

[0019] When the coating is just applied, the emulsifier in the coating causes the oil on the metal surface to saponify and separate, so that the coating can adhere well to the steel surface. At the same time, the aromatic sulfinic acid acts on the grease, so that it has good adsorption capacity when it is just applied. After a period of time, the zinc powder contacts the steel and the zinc begins to corrode first. The corroded zinc will produce zinc oxide ions, forming a weak alkaline environment. In the weak alkaline environment, the grease will be saponified, which will easily affect the adsorption of the coating. The aromatic sulfinic acid can effectively inhibit the formation of the alkaline environment in this process, so that the coating still has good adsorption capacity after long-term use. Example

[0020] The oil-containing anti-rust coating provided in this embodiment has a total mass of 300g, and each component is mixed according to the total mass fraction. 1.1% of dispersant, 1.4% of ultrafine composite titanium dioxide, 0.8% of ultrafine ferrophosphorus powder, 3% of ultrafine barium sulfate, 3% of ultrafine zeolite powder, and 5% of talcum powder are put into the device and mixed evenly.

[0021] The above mixture is added with 0.4% hydroxyethyl cellulose, 3.4% silane coupling agent with epoxy functional group, 45% film-forming substance, 0.6% emulsifier and deionized water, mixed and stirred evenly and ultrasonically treated to obtain mixture A. The stirring speed of the stirrer is between 800-1200r / min. The ultrasonic treatment temperature is 0-35°C and the ultrasonic treatment time is 8-14h.

[0022] Add 2% of arylsulfonyl chloride to 4% of zinc powder and stir evenly, control the temperature at 140°C, and stir for 10 minutes to obtain substance B. The chemical formula of the reaction between arylsulfonyl chloride and zinc is: .

[0023] Mix substance A and substance B together, stir at high speed and filter to obtain the coating. The stirring speed of the mixer is between 3000-4000r / min. The filter aperture is 130 mesh. Example

[0024] The oil-containing anti-rust coating provided in this embodiment has a total mass of 300g, and each component is mixed according to the total mass fraction. 1.1% of dispersant, 1.4% of ultrafine composite titanium dioxide, 0.8% of ultrafine ferrophosphorus powder, 3% of ultrafine barium sulfate, 3% of ultrafine zeolite powder, and 5% of talcum powder are put into the device and mixed evenly.

[0025] The above mixture is added with 0.4% hydroxyethyl cellulose, 3.4% silane coupling agent with epoxy functional group, 45% film-forming substance, 0.6% emulsifier and deionized water, mixed and stirred evenly and ultrasonically treated to obtain mixture A. The stirring speed of the stirrer is between 800-1200r / min. The ultrasonic treatment temperature is 0-35°C and the ultrasonic treatment time is 8-14h.

[0026] Add 1.5% of arylsulfonyl chloride, 5.2% of zinc powder and 0.3% of graphene and stir evenly. The temperature is controlled at 140°C. During stirring, the stirring kettle is connected to a positive power supply, the stirring rod is connected to a negative power supply, and the stirring kettle and the stirring rod are insulated. The voltage is controlled at 60V. Stir for 10 minutes to obtain substance B. The chemical formula of the reaction between arylsulfonyl chloride and zinc is When electricity is turned on, graphene and zinc powder can be connected more easily, so that after the coating is applied, more zinc powder is connected to the metal, thereby enhancing the anti-corrosion effect.

[0027] Mix substance A and substance B together, stir at high speed and filter to obtain the coating. The stirring speed of the mixer is between 3000-4000r / min. The filter aperture is 130 mesh. Example

[0028] The oil-containing anti-rust coating provided in this embodiment has a total mass of 300g, and each component is mixed according to the total mass fraction. 1.1% of dispersant, 1.4% of ultrafine composite titanium dioxide, 0.8% of ultrafine ferrophosphorus powder, 3% of ultrafine barium sulfate, 3% of ultrafine zeolite powder, and 5% of talcum powder are put into the device and mixed evenly.

[0029] The above mixture is added with 0.4% hydroxyethyl cellulose, 3.4% silane coupling agent with epoxy functional group, 45% film-forming substance, 0.6% emulsifier and deionized water, mixed and stirred evenly and ultrasonically treated to obtain mixture A. The stirring speed of the stirrer is between 800-1200r / min. The ultrasonic treatment temperature is 0-35°C and the ultrasonic treatment time is 8-14h.

[0030] Add 2% of arylsulfonyl chloride to 4% of zinc powder and 1% of graphene and stir evenly. The temperature is controlled at 140°C. During stirring, the stirring kettle is connected to a positive power supply, the stirring rod is connected to a negative power supply, and the stirring kettle and the stirring rod are insulated. The voltage is controlled at 60V. Stirring time is 10 minutes to obtain substance B. The chemical formula of the reaction of arylsulfonyl chloride and zinc is: .

[0031] Mix substance A and substance B together, stir at high speed and filter to obtain the coating. The stirring speed of the mixer is between 3000-4000r / min. The filter aperture is 130 mesh.

[0032] After testing, four kinds of coatings were tested for anti-shedding using a Baige tester. Increasing the content of arylsulfonyl chloride can improve the anti-shedding ability of the coating to a certain extent, maintain the strong adhesion of the coating and effectively prevent the metal from corroding due to contact with oxygen. At the same time, the addition of graphene increases the conductivity between zinc and metal, further enhancing the anti-corrosion effect.

[0033] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that an article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such article or device. In the absence of further restrictions, the elements defined by the sentence "include..." do not exclude the existence of other identical elements in the article or device including the elements.

[0034] The above embodiments are only used to illustrate the technical solution of the present invention and are not intended to limit the present invention. The present invention is described in detail with reference to the preferred embodiments. It should be understood by those skilled in the art that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, and should be included in the scope of the claims of the present invention.

Claims

1. An oil-based anti-rust paint, characterized in that: It includes a main agent and an auxiliary agent, wherein the main agent formula is: hydroxyethyl cellulose, a silane coupling agent with epoxy functional groups, an emulsifier, a dispersant, and ultrafine composite titanium dioxide, ultrafine ferrophosphorus powder, ultrafine barium sulfate, ultrafine zeolite powder, talcum powder, nano pigments, and film-forming substances; The chemical formula of the additive is The aromatic sulfonyl chloride is added with zinc powder, stirred evenly and then added to the main agent, so that the aromatic sulfonyl chloride in the auxiliary agent is partially converted into aromatic sulfinic acid.

2. The oil-based anti-rust paint according to claim 1, characterized in that: When the aromatic sulfonyl chloride and the zinc powder are stirred, the temperature is controlled between 130° C. and 140° C., and the stirring time is 8 to 10 minutes.

3. The oil-based anti-rust paint according to claim 1, characterized in that: Graphene is added to the additive, and graphene and zinc powder are added to arylsulfonyl chloride at the same time and stirred evenly. During stirring, the stirring kettle is connected to a positive power supply, the stirring rod is connected to a negative power supply, and the stirring kettle and the stirring rod are insulated, and the input voltage is controlled at 60V.

4. The oil-based anti-rust paint according to claim 1, characterized in that: According to the mass percentage, the main agent content is 93%-95%, the auxiliary agent content is 5%-7%, the zinc powder content in the auxiliary agent is 4%-5%, and the ratio of aromatic sulfonyl chloride to aromatic sulfinic acid is 0.5-0.8:

1.

5. The oil-based anti-rust paint according to claim 4, characterized in that: The mass percentages of the components in the main agent are: 0.3%-0.7% hydroxyethyl cellulose, 1.2%-6.2% silane coupling agent with epoxy functional group, 0.5%-1% emulsifier, 0.8%-1.5% dispersant, 1%-2% ultrafine composite titanium dioxide, 0.6%-1% ultrafine ferrophosphorus powder, 2%-4% ultrafine barium sulfate, 3%-5% ultrafine zeolite powder, 4%-6% talc, 0.5%-2% nano pigment, and 30%-50% film-forming substance.

6. A method for preparing the oil-containing anti-rust coating according to any one of claims 1 to 5, characterized in that: Step S00: putting dispersant, ultrafine composite titanium dioxide, ultrafine ferrophosphorus powder, ultrafine barium sulfate, ultrafine zeolite powder and talcum powder into the device according to mass fraction and mixing them evenly; Step S10: adding hydroxyethyl cellulose, a silane coupling agent having an epoxy functional group, a film-forming substance, an emulsifier, and deionized water to the above mixture, mixing and stirring the mixture evenly, and ultrasonically treating the mixture; Step S20: adding zinc powder to arylsulfonyl chloride and stirring evenly, controlling the temperature between 130°C and 140°C, and stirring for 8-10 minutes; Step S30: mixing the uniformly mixed auxiliary agent and the main agent together, stirring at high speed to uniformly obtain the coating after filtering; Step S40: adding nano pigments of different colors into the above coating to obtain coatings of different colors.

7. The method for preparing the oil-containing anti-rust coating according to claim 6, characterized in that: In step S20, graphene is added, and graphene and zinc powder are added to aromatic sulfonyl chloride at the same time and stirred evenly. During stirring, the stirring kettle is connected to a positive power supply, the stirring rod is connected to a negative power supply, and the stirring kettle and the stirring rod are insulated, and the input voltage is controlled at 60V.